Adesp. 741 K.-A. Niektóre aspekty stylistyki komediowej - Bartol, Krystyna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
This article explores the thematic and stylistic function of the anaphora in the anonymous fragment of Old Comedy (741 K.-A.). It also analyses an interpretation of Plutarch’s comment on these lines.